QUANTITATIVE ANALYSIS OF SECRETORY APPARATUS ULTRASTRUCTURAL CHANGES OF RAT ATRIAL CARDIOMYOCYTES UNDER THE INFLUENCE OF CHRONIC PRENATAL HYPOXIA DURING ONTOGENETIC STAGES - Шевченко К. М. (World of Medicine and Biology, 2015)
Intrauterine hypoxia leads to infant mortality and developmental abnormalities and postnatal deficits. Atrial cardiomyocytes take part in maintaining of circulating blood volume due to their secretory activity. Because of release of atrial natriuretic peptide from cardiomyocytes is induced by myocardial stress the plasma level of this peptide is used as diagnostic marker in the clinical setting to monitor the severity of hypertrophy and congestive heart failure.The task of this study was quantitative ultrastructural analysis of secretory apparatus of rat atrial cardiomyocytes under the influence of chronic prenatal hypoxia during the stages of ontogenesis. We used rat`s embryo hearts on 14th, 16th and 18th embryonic day, hearts of newborn rats and hearts of the rats on the 3rd, 14th and 30th day of postnatal ontogenesis. Induction of chronic hypoxia was made by standard method. Pregnant females were injected by 1% sodium nitrite solution subcutaneous in dose of 5 mg per 100 g of weight from 10th to 21th embryonic day. Fetal hearts were fixed at 2.5% glutaraldehyde solution, postfixed in 1% OsO4 («SPI», США) and embedded in Epon-812 according to standard protocol. The study was conducted using a transmission electron microscopy.Quantitative ultrastructural analysis showed that under the conditions exposure of chronic hypoxia from the 16th to the 18th day of prenatal development in rat atrial cardiomyocytes the ratio of various types of granules shifted to type I. It is followed by excess of relative volume of the Golgi complex over the volume of secretory granules. We suggested that chronic hypoxia stimulated synthesis of ANP directly involved factors HIF and by compensatory mechanisms were included in response to reduced oxygen saturation. These changes of secretory activity of the atrial cardiomyocytes were transient and gradually tend to the norm on the 3rd day of postnatal development after the exposure of harmful factor.Thus, intrauterine chronic hypoxia stimulates secretion of atrial natriuretic peptide during prenatal ontogenesis. However, morphological changes are transient and tend to the values the control group on the 3rd day of postnatal development after the exposure of harmful factor.
Keywords: rats; atrial cardiomyocytes; secretory granules; prenatal hypoxia; cardiogenesis